A high performance liquid chromatography method for simultaneous detection of 20 bioactive components in tea extracts. Issue 21 (22nd August 2019) - Nian, Bo; Chen, Lijiao; Yi, Chao; Shi, Xingyun; Jiang, Bin; Jiao, Wenwen; Liu, Qianting; Lv, Caiyou; Ma, Yan; Zhao, Ming
Abstract: Tea is the second most widely consumed beverage and contains various bioactive compounds. A simple method to analyze these compounds is of great scientific and commercial interest. In this work, a 30 min HPLC method was developed using a simple gradient elution system, and the mobile phases and elution gradients were optimized. This method separated 17 polyphenols and three alkaloid compounds in tea extracts, including catechins, alkaloids, phenolic acids, flavonols, and flavone, which are responsible for the bioactivity and flavor of tea. Excellent linearity was observed for all standard calibration curves, and correlation coefficients were above 0.9994. Heatmap analysis demonstrated significant separation between green, black, and pu‐erh tea samples. The method described here is accurate and sensitive enough for the determination of active components in tea and could potentially be applied to other food products for the comprehensive investigation of their quality.